2012
DOI: 10.3109/0284186x.2012.746466
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body mass index and alcohol and tobacco consumption among breast cancer survivors and cancer-free women: A prospective study in the Danish Diet, Cancer and Health Cohort

Abstract: Background . A breast cancer diagnosis has been suggested as a teachable moment when a woman is more open to making healthier lifestyle changes. Little is known about the health behaviour changes women with breast cancer initiate compared to those made by other women. Material and methods . We examined changes in body mass index (BMI) and tobacco and alcohol consumption among women with a diagnosis of breast cancer and among cancer-free women. We used data from 23 420 women aged 50 -64 years who participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 24 publications
2
46
2
Order By: Relevance
“…Dietary and alcohol intakes of cancer survivors have received increasing attention in the last decade 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Overall, these studies tended to suggest an improvement in dietary behavior after cancer diagnosis, as well as a strong motivation of cancer survivors to make lifestyle changes 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary and alcohol intakes of cancer survivors have received increasing attention in the last decade 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Overall, these studies tended to suggest an improvement in dietary behavior after cancer diagnosis, as well as a strong motivation of cancer survivors to make lifestyle changes 4.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these studies tended to suggest an improvement in dietary behavior after cancer diagnosis, as well as a strong motivation of cancer survivors to make lifestyle changes 4. However, most of these studies were cross‐sectional and either compared survivors to cancer‐free subjects11, 13, 15, 16, 17, 18, 21, 26 or described only postdiagnosis dietary and alcohol intakes in cancer survivors 10, 12, 14, 19, 23. Although a few studies provided information on the variation of dietary and/or alcohol intakes between before and after cancer diagnosis,20, 22, 24, 25, 27, 28, 29 they reported retrospective or qualitative self‐reported changes, that are possibly prone to recall bias.…”
Section: Introductionmentioning
confidence: 99%
“…36 Another study found that mean tobacco consumption decreased by 1.1 grams per day at up to 6 years after a breast cancer diagnosis and that the percentage of women who did not smoke increased by 7%. 37 These positive changes may in part be due to physician's focus on smoking cessation. In a recent analysis of risk factors in cancer survivors, including breast cancer survivors, it was found that 87% of current smokers reported discussing smoking cessation with their physicians.…”
Section: Health-related Behaviors After a Dcis Diagnosismentioning
confidence: 99%
“…Among women in a Danish cohort with grades I-III breast cancer, alcohol consumption increased by 0.6 grams/day after diagnosis. 37 In the Norwegian Women and Cancer cohort study, Skeie et al found that after a breast cancer diagnosis, women significantly increased their fruit and vegetable consumption, compared to women who remained cancer-free. 36 …”
Section: Health-related Behaviors After a Dcis Diagnosismentioning
confidence: 99%
“…An English study focusing on cancer found that diagnosis did not change the prevalence of daily or near daily alcohol use (Williams et al, 2013). A Danish study also found no change in alcohol consumption after a cancer diagnosis compared to the rest of the sample (Bidstrup et al, 2013). Among adults ages 50 and over, findings from the U.S. Health and Retirement Study showed declines in excessive alcohol consumption after diagnosis of cancer, diabetes, and stroke (Newsom et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%